Risk factors for prostate cancer in Kohgiluyeh and BoyerAhmad provinces, Iran - Hassan Askarpour; Mohammad Hassan Lotfi; Hossein Fallahzadeh; Masoud Amiri; Dariush Bastam (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Prostate cancer is the most common malignant cancer and the second most common cancerin men worldwide. It is the second leading cause of death after lung cancer in men. This study performed todetermine the risk factors for prostate cancer in Kohgiluyeh and Boyer-Ahmad provinces.Method: The present study was a retrospective and case-control study in which 80 prostate cancer patientsand 140 controls matched in Kohgiluyeh and Boyer-Ahmad provinces. Data collected using a questionnaireand interviewed by the researcher. To analyze the data, Chi-square and logistic regression tests with oddsratio with 95% confidence conducted using SPSS v.22 software.Results: The results showed that in the univariate conditional logistics analysis, The highest odds ratiofor prostate cancer related to red meat consumption 2-4 times a week (95% CI: 2.60 – 26.40) was 20.74and The smallest odds ratio was related to continuous physical activity 0.34 ( 95% CI: 0.19 – 0.61). Inthe multivariate conditional logistic regression model, after removing the confounding variables, it wasobserved that the history of pelvic imaging, red meat consumption 2-4 times a week, fast food consumptionand processed meat consumption 2-4 times a week, Family history of prostate cancer, history of urogenitalinfections were identified as the most effective factors in prostate cancer.Conclusion: Family history of prostate cancer, history of urinary tract infection, history of smoking, historyof pelvic imaging, consumption of red meat, consumption of fast food and processed meats were the mostimportant predictors of prostate cancer in this study. It can be considered by educational and health plannersto prevent this cancer and take appropriate intervention measures.